Case Report: A case of influenza A infection-associated stiff person spectrum disorder with favorable outcome - Liu, Xiaoqian; Lei, Meifang; Tian, Mengna; Zhang, Yanfen; Yu, Xiaoli; Li, Dong (Frontiers in Immunology, 2025)
Influenza A (H1N1) virus infection has been associated with various immune-mediated neurological disorders. Previous studies have reported cases of stiff person spectrum disorder (SPSD) subsequent to viral infections. We report a case of a 4-year-old boy who developed SPSD following H1N1 infection. The patient primarily presented with axial and limb muscle rigidity, painful spasms, and exaggerated startle responses. Electromyography (EMG) revealed continuous synchronous discharges in agonist and antagonist muscles, consistent with the characteristic manifestations of stiff person syndrome (SPS), meanwhile, repetitive compound muscle action potentials (R-CMAPs) following stimulation of the median, common peroneal and tibial nerves were observed on electroneurography (ENG). Symptoms markedly improved following benzodiazepine therapy, and complete remission was achieved after combined treatment with IVIG and glucocorticoids.